'SIMLA' Educational Game-Based Learning Media for the Inculcation of Pancasila Symbols and Principles, Augmenting Independent Character - Diah Aulia Azizatur Rohmah; Sri Untari; Ade Eka Anggraini (LPPM Undiksha, 2024)
The transition from the K13 curriculum to an independent curriculum creates problems, especially in the learning process and learning media. A learning process needs to be supported by good learning media to achieve learning goals. This research aims to develop the educational game learning media